Development and Testing of the Kids Hurt App, a Web-Based, Pain Self-Report App for First Nations Youths: Mixed Methods Study - Karlee Francis; Julie Francis; Margot Latimer; Hayley Gould; Shante Blackmore; Emily MacLeod (JMIR Human Factors)
Abstract BackgroundFirst Nations children and youths may have unique ways to convey their health needs that have not been recognized by health providers. This may contribute to the disparity between high rates of mental health and physical pain and low rates of treatment for the conditions they experience. Evidence suggests that a colonial history has resulted in poor experiences with the health care system, lack of trust with health providers, and miscommunication between clinicians and patients. Contemporary ways, using both Indigenous and Western knowledge, are needed to bridge the gap in communicating pain. ObjectiveThe aim of this qualitative study was to test the usability and clinical feasibility of the Kids Hurt App with First Nations youths and clinicians working with youths. MethodsUsing a Two-Eyed Seeing approach, the Kids Hurt App was developed using concepts from validated mood and pain assessment apps combined with community-based research that gathered First Nations youths and clinicians perspectives on quality, intensity, and location of pain and hurt. The Kids Hurt App contains 16 screens accessible on any web-based device. ResultsIn total, 3 rounds of low-fidelity testing (n=19), 2 rounds of high-fidelity testing (n=20), and 2 rounds of clinical feasibility testing (n=10) were conducted with First Nations youths (10‐19 years) to determine the relevance, validity, and usability of the Kids Hurt App. High-fidelity testing was also conducted with 15 clinicians after completing the high-fidelity youth sessions. Youths had constructive suggestions that were used to improve the app in subsequent rounds of version testing. There was one main discrepancy between youths and clinicians related to preference for how best to visually convey pain. The youth’s preference was maintained in the app. ConclusionsAll youths in all rounds of testing indicated that they would use the Kids Hurt App if it was available to them in a health care setting, with most clinicians noting that the app would be useful in practice.